Conceptualizing eWOM, Brand Image, and Brand Attitude on Consumers Willingness to Pay in the Low-Cost Airline Industry in Thailand - Somcanae Yodpram; Nuchjarin Intalar (My University, 2020)
The expansion usage of the Internet, especially social media, has extended customers options for gathering products and services information by including other customers' comments and opinions posted on the Internet. Customers are able to share their experience, perception, and advice by involving in electronic word-of-mouth (eWOM) on their social media and websites that facilitate reviewing of consumer's experiences, which can be reached by their friends and other potential customers. This study reviews literature related to eWOM, brand attitude, brand image, brand loyalty, and their implication on the willingness to pay premium ticket price in the context of the low-cost airline industry in Thailand. Existing literature presented that eWOM, as well as, brand image have positive influences on customer's repurchase intention. In addition, brand attitude and brand loyalty also influence customers' intention to buy for a particular product. This leads to the motivation to formulate a conceptual framework to explore the relationships between the mentioned independent variables on the willingness to pay more on airline ticket price. This conceptual framework also suggests methodology and sample groups for further research investigation.
Keywords: Ticket; Brand Loyalty; Conceptual framework; Conceptual model; Digital Marketing and Social Media